Resolution of Dispute Resolution on the Status of Child Adoption Deeds by PTUN Serang - Muhammad Dzul Faqar; Nurikah Nurikah; Ahmad Rayhan (Jurnal Hukum Prasada, 2026)
This study aims to analyze the decision of the Serang State Administrative Court Number 31/G/2023/PTUN. SRG in a dispute over the adoption deed of a child arising from maladministration of the inclusion of status on the deed. The problem focuses on the misapplication of the law by state administrative officials and the position of PTUN decisions as a guideline for resolving administrative disputes based on the principle of contrarius actus, which is the authority of TUN officials who issue decisions to cancel or correct. This study uses an empirical juridical method with a qualitative approach. Data was obtained through a study of documents on court decisions and laws and regulations that were the basis for the judge's consideration, as well as interviews with the Serang PTUN judge who was involved in the examination of the case. The analysis was conducted to assess the suitability between legal norms and their application in population administration practices. The results of the study show that the court decision provides legal certainty to the plaintiff for the error in the inclusion of status in the child adoption certificate. Based on the principle of contrarius actus, officials of the Population and Civil Registration Office are obliged to correct administrative errors, as well as deactivate and revoke Decree Number 474.1/819-Cs/1999 concerning the birth certificate concerned. This decision affirms the importance of TUN officials' compliance with the principles of legality and protection of citizens' rights in the implementation of state administration.